The Role of Investment Literacy, Perceived Risk, and Perceived Benefit in Shaping Online Investors' Intention to Use the Bibit Robo-Advisor Application - Arpinda, Nadhyre; Juita, Verni (Universitas Negeri Padang, 2025)
This study aims to examine the impact of investment literacy, perceived risk, and perceived benefit on the intention to invest using the Bibit robo-advisor application among potential investors in Indonesia. As the use of robo-advisors increases, understanding the factors that influence investment intentions can provide valuable insights for both developers and financial educators. A quantitative survey was conducted, gathering responses from 450 participants through various online channels, including social media platforms. The data were analyzed using SmartPLS 4.0 software to assess the relationships between the variables. The findings indicate that both investment literacy and perceived benefit have significant positive effects on individuals' interest in investing with Bibit Robo advisor application. This highlights the importance of investors financial knowledge and their perceived benefit in the decision-making process regarding robo advisor adoption. Conversely, perceived risk did not show a significant effect on investment interest, suggesting that concerns about risk may not strongly influence the decision to use robo-advisors for investment purposes. These insights enhance our understanding of the factors driving robo-advisor adoption. They may help inform strategies to improve financial literacy and highlight the perceived benefits of these platforms.